Distribution of different plant life forms on tropical islands: patterns and underlying mechanisms - Yang, Chengfeng; Zhao, Jingyan; Huang, Shengzhuo; Zhou, Shurong; Cheng, Yikang (Frontiers in Plant Science, 2025)
IntroductionIsland biogeography theory posits that both island area and isolation significantly influence species distribution patterns and community structure. This study investigates the effects of island area and isolation on plant community structure, specifically focusing on the variation in species richness and abundance among different plant life forms (i.e., trees and shrubs) on tropical islands in the South China Sea.MethodsWe surveyed woody plants and collected soil samples from 20 tropical islands in the South China Sea, analyzing how island area, isolation, climate and soil factors influence plant communities across different life forms (trees vs. shrubs).ResultsThe results indicate that species richness increases with island area and decreases with isolation, which aligns with the classic predictions of island biogeography. However, plant abundance exhibits a more complex pattern: tree abundance is positively correlated with island area and negatively correlated with isolation, while shrub abundance shows the opposite trend. Furthermore, the relative tree richness and abundance are predominant on larger, less isolated islands, whereas shrubs are more prevalent on smaller, more remote islands. These contrasting patterns suggest that different life forms adopt distinct ecological strategies within island ecosystems. The structural equation model (SEM) revealed that island area, isolation, and climatic factors directly affect the richness and abundance of trees but not shrubs. Additionally, the indirect effect of soil pH has proven to be a crucial environmental factor in shaping plant community structure.DiscussionOverall, this study highlights the multifaceted roles of geographic, climatic, and soil factors in determining the composition of island plant communities across different life forms. The findings have important implications for island conservation, as they provide a deeper understanding of how plant communities respond to spatial and environmental factors, aiding in the management of biodiversity on tropical islands.